Implementasi Kebijakan Undang-Undang Nomor 24 Tahun 2011 tentang Sistem Jaminan Sosial Nasional terhadap Penggunaan Mobile JKN di Puskesmas Maiwa - Nur Zahira; Harianti Hamid; Sundari, Sundari; Muhammad Nur (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the implementation of policies on the national social security system on the use of Mobile JKN in the Maiwa Health Center. The population in this study is 22,791 participants who are registered JKN participants in 2024. The sampling technique used random sampling of 100 respondents. This type of research is quantitative deductive. The data collection techniques used in this study were observation, questionnaire, and literature study. The data analysis technique used was a validity and reliability test using the help of the IBM SPSS statistical 26.0 application. The results of this study show that there is a strong relationship between the implementation of